1984
DOI: 10.1152/jappl.1984.56.5.1302
|View full text |Cite
|
Sign up to set email alerts
|

A modified anaerobic method of sweat collection

Abstract: In an attempt to devise a method for collecting large volumes of thermally induced sweat with less epidermal contamination and evaporative water loss, we developed an anaerobic sweat collector by using a sheet of polyethylene film placed over a thin layer of Vaseline and paraffin oil on the skin. To test the validity of the new method, sweat samples collected every 5 min from the new collector (sweat A) were compared with those obtained from a second collector using no oil (sweat B) and scraped sweat for conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
72
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 0 publications
2
72
0
Order By: Relevance
“…It is possible that the resultant sweat available for analysis contains some contamination from the absorbent pad and may give rise to false positive or false negative results (Brisson et al 1991). In the present study, this issue was circumvented by allowing the sweat to pool during the collection period before aspiration, thus negating any potential contamination from collection pads (Boysen et al 1984). Furthermore, we employed a 20 minute washout sweat collection period to allow for any epidermal or sweat gland derived protein debris to be removed prior to collecting the main sweat sample for analysis.…”
Section: Discussionmentioning
confidence: 95%
“…It is possible that the resultant sweat available for analysis contains some contamination from the absorbent pad and may give rise to false positive or false negative results (Brisson et al 1991). In the present study, this issue was circumvented by allowing the sweat to pool during the collection period before aspiration, thus negating any potential contamination from collection pads (Boysen et al 1984). Furthermore, we employed a 20 minute washout sweat collection period to allow for any epidermal or sweat gland derived protein debris to be removed prior to collecting the main sweat sample for analysis.…”
Section: Discussionmentioning
confidence: 95%
“…They also showed that autologous sweat was able to induce histamine release from basophils, which correlated with the size of the positive ASwST, implying the sweat itself contains factors that can induce histamine release. 14 Adachi et al collected sweat as described by Boysen et al, 15 who described an anaerobic method of collecting large volumes of sweat with less epidermal contamination. They heated the area with a hair dryer and constructed a sweat collector out of petroleum jelly and paraffin oil covered by polyethylene film attached to rubber tubing and a syringe.…”
Section: Discussionmentioning
confidence: 99%
“…They heated the area with a hair dryer and constructed a sweat collector out of petroleum jelly and paraffin oil covered by polyethylene film attached to rubber tubing and a syringe. 15 Otherwise, published articles on the methods of ChU and sweat collection are lacking in further details. 14,16 Therefore, this is the first study using PI for sweat collection to perform ASwST.…”
Section: Discussionmentioning
confidence: 99%
“…Sweat samples were collected every 2–4 min by scratching their foreheads with micro-tubes, and subjects’ foreheads were wiped and cleaned with gauze after every sweat collection 19 . The changes of [Na + ] and [K + ] during euhydration and dehydration trials were also studied ex situ in the same manner.…”
Section: Methodsmentioning
confidence: 99%
“…Sweat analysis is currently used for applications such as disease diagnosis, drug abuse detection, and athletic performance optimization 13 . For these applications, the sample collection and analysis are performed separately, failing to provide a real-time profile of sweat content secretion, while requiring extensive laboratory analysis using bulky instrumentation 19 . Recently, wearable sweat sensors have been developed, with which a variety of biosensors have been used to measure analytes of interest (Supplementary Table 1) 1418 .…”
mentioning
confidence: 99%